Pengujian Moderasi Komitmen Organisasi untuk Peningkatan Akuntabilitas Kinerja Instansi Pemerintah Kabupaten Serang - Mutaqin, Riansyah; Prahiawan, Wawan; Mumtazah Damarwulan, Liza (Fakultas Ekonomi Universitas Gresik, 2023)
The aims of this research are: (1) to examine and analyze the effect of Apparatus Competence on Performance Accountability of Government Agencies, (2) to test and analyze the ability of Organizational Commitment to moderate the relationship between Apparatus Competence and Government Agencies Performance Accountability. The research was conducted at 29 OPD in the Government of Serang Regency using quantitative methods through data analysis using the Partial Least Square (PLS) based Structural Equation Model (SEM) method, while a sample of 145 people used the census method. This study obtained the results that Apparatus Competence has a positive and significant effect on Government Agencies Performance Accountability, Organizational Commitment is also able to moderate the relationship between Apparatus Competence and Government Agencies Performance Accountability.